2016
DOI: 10.3390/su8090857
|View full text |Cite
|
Sign up to set email alerts
|

The Multilevel Index Decomposition of Energy-Related Carbon Emission and Its Decoupling with Economic Growth in USA

Abstract: Abstract:The United States of America is not only an important energy consuming country, but also in the dominant position of energy for many years. As one of the two largest emitters, the US has always been trying to register a decline in energy-related CO 2 . In order to make a further analysis of the phenomenon, we choose a new decoupling analysis with the multilevel logarithmic mean Divisia index (LMDI) method. This study examined the contribution of factors influencing energy-related carbon emissions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 59 publications
0
15
0
1
Order By: Relevance
“…Actually, decoupling research based on the LMDI approach is more extensive due to no residual after decomposition. 26 For instance, Jiang et al 27 measured the decoupling of carbon emissions from economic output in the U.S. by means of combining the LMDI method with the decoupling indicator advanced by Vehmas et al. 17 The results indicated that population exerted a negative effect on the decoupling process while energy intensity played a positive role in the decoupling process, by contrast, energy structure and carbon intensity have no obvious influence pattern.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Actually, decoupling research based on the LMDI approach is more extensive due to no residual after decomposition. 26 For instance, Jiang et al 27 measured the decoupling of carbon emissions from economic output in the U.S. by means of combining the LMDI method with the decoupling indicator advanced by Vehmas et al. 17 The results indicated that population exerted a negative effect on the decoupling process while energy intensity played a positive role in the decoupling process, by contrast, energy structure and carbon intensity have no obvious influence pattern.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This facilitates answering question iii). For this, a decoupling index is calculated as of a second decomposition of the results obtained from the LMDI I analysis (Diakoulaki and Mandaraka, 2007;Jiang et al, 2016;Cansino and Moreno, 2017;Román-Collado et al, 2018a). The main methodological contribution lies in the fact that this is the first time that a comprehensive model is undertaken as described, which includes the LMDI, the IAA and the decoupling analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Long [16] refers to resource consumption and environmental pollution as ecological loss and analyzed the economic growth, ecological loss and welfare levels in the process of urbanization. The remaining scholars use the decoupling index to analyze the relationship between economy and environment, such as the impact of economic, energy and environmental factors on eco-efficiency performance indicators [17], economic growth and groundwater consumption [18], economic growth and environmental pollution [19], economic growth and environmental pressure [20], and economic growth and environmental conditions [21].…”
Section: Introductionmentioning
confidence: 99%